Knowledge, Attitudes, and Practices of Health Personnel in Responding to the COVID-19 Pandemic in Indonesia - Suryani, Dyah; Suyitno, Suyitno; Maretalinia, Maretalinia; Juliansyah, Elvi; Saki, Vernonia Yora; Tantrakarnapa, Kraichat (Kesmas, 2021)
The COVID-19 pandemic, originated in China, has spread to worldwide, including Indonesia. Until July 2021, the growth rate has been gradually increasing, and cases have been found in all 34 provinces of Indonesia. This cross-sectional study aimed to investigate the knowledge, attitude, and practices (KAP) of health personnel in the primary health care towards the COVID-19 pandemic in Indonesia using online self-report questionnaire. A total of 440 respondents contributed to this online survey. The average level of KAP were 7.7 out of 10.0, 14.3 out of 15.0, and 31.9 out of 36.0, respectively. There was no significant association between respondents’ characteristics (sex, marital status, and age) and their KAP for all variables showed p-value>0.05. It can be concluded that the level of KAP was good, despite the respondents’ characteristics that had no association with KAP.